Children's achievement in rural and urban areas of Peru - Cueto, Santiago (1997)
This paper presents the results on four tests of students from fourth and fifth grade of eight urban and rural elementary schools. Four of the schools were located in rural Huaraz, two were urban public schools (one in Huaraz and one in Lima), one was a parochial school and one was a privare school (these last two in Lima). The tests measured cognitive processes (coding from the WISC-R) and achievement (reading comprehension, vocabulary and arithmetic). The results favored urban over rural students. Among the urban, the highest scores were for the students of the privare and parochial schools. Girls scored significandy less than men in sorne of the rural schools. Overall, more than gender differences, the results showed a significandy poorer performance for the rural students.